Existing Voice Solutions and Evolution for LTE Terminal - Jing Zhou; Yu Shi (Dianxin kexue)
As the final voice solution for LTE,VoLTE has become the key research point of the industry.Several existing voice solutions of LTE user equipment were compared and analyzed in details.Technical advantages and unsolved problems of VoLTE which is based on pure PS network and IMS system were mainly discussed from the prospective of the LTE terminal.The technical characteristics and evolution direction of VoLTE were mentioned in the end.